Prevalence of Methicillin Resistant Staphylococcus Aurous In Surgical Units of a Tertiary Care Hospital - Dixit, Dr. N. S.; Kothari, Dr. Deepak; Chandrakar, Dr. Karan Singh (International Journal of Innovative Research in Medical Science, 2017)
Background - Staphylococcus aureus is a dangerous pathogen for both community-acquired as well as hospital-associated infections. Methicillin-resistant Staphylococcus aureus (MRSA) is widely recognized as one of the pathogens causing hospital- and community- acquired infections. Due to increased incidence of MRSA vancomycin has been used as an empirical treatment for Staphylococcus aureus infections which in turn results in the emergence of VRSA (vancomycin resistant Staphylococcus aureus). It is necessary to know the prevalence of MRSA and its antibiotic sensitivity pattern for proper treatment of the patients and thereby reducing the morbidity and mortality of the patients in our tertiary care hospital. Methods - A total of 796 sample from the OPD and IPD patients attending the surgery department from various clinical specimens from January 2015 to Feb 2017. All samples were sent to microbiology laboratory for identification and antibiotic susceptibility pattern testing. Results were obtained from the microbiology department as resistant and susceptible according to zone of inhibition shown by the strain. Results - Of the total 796 samples collected from the surgery department 254 Staphylococcus aureus were isolated of which 96 (37.79%) were MRSA and 158 (62.20%) were MSSA (Methicillin sensitive Staphylococcus aureus). Of the total 96 MRSA strains 74 strains (77.08%) were multidrug resistant. MRSA strains were more resistant to other antibiotics than MSSA strains. No strain was resistant to vancomycin. Conclusion - MRSA strains are more prevalent in tertiary care hospital and multidrug resistant MRSA prevalence is higher in surgical units. The most effective way to prevent MRSA is surveillance of antibiotic resistance profiles of Staphylococcus aureus and there should be formulation of antibiotic policy in the hospital.